Pengaruh Budaya Oraganisasi, Kepuasaan Kerja, Kompensasi, Motivasi, lingkungan kerja Terhadap Kinerja Karyawan Pada CV Rindang Khatulistiwa Jember - Wulandari, Putri; Maspufah, Hayatul; ., Muhdar (GLOBAL SCIENTS PUBLISHER, 2026)
Performance is a key factor for an institution, determining the achievement of high-quality work results toward organizational goals. This study aims to determine the influence of organizational culture, job satisfaction, compensation, motivation, and the work environment on employee performance at CV Rindang Khatulistiwa Jember. The method used in this study is a quantitative approach. Sampling was conducted using a saturated sampling technique, with a sample size of 61 employees, representing the total number of employees. Data collection used a questionnaire with a Likert scale research instrument. The research data was analyzed using SPSS 25, using several testing techniques: data instrument testing, classical assumption testing, multiple linear regression testing, coefficient of determination (R2) testing, and hypothesis testing. The research findings indicate that job satisfaction, compensation, and the work environment have a partial effect on employee performance. Meanwhile, organizational culture and motivation do not have a partial effect on employee performance. However, the variables of organizational culture, job satisfaction, compensation, motivation, and the work environment simultaneously influence employee performance. These results are expected to contribute to efforts to evaluate targeted human resource and employee management.